2011
DOI: 10.1159/000330175
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Arterial Matrix Metalloproteinases Leads to Vascular Calcification in Chronic Kidney Disease

Abstract: Background: The objective of the current study was to determine if altered regulation of matrix metalloproteinases (MMPs) may predispose to extracellular matrix degradation, facilitating arterial calcification in chronic kidney disease (CKD) using a progressive model of CKD-MBD, the Cy/+ rat. Methods: Sera were collected from normal or CKD rats at various times and MMP-2 and MMP-9 levels determined by ELISA or zymography. Aorta tissue was harvested at sacrifice for RT-PCR and immunostaining. Calcification of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 40 publications
3
73
0
Order By: Relevance
“…Interestingly, experimental evidence showed an early upregulation of MMP-2 expression in areas of elastin degradation and smooth muscle cells phenotype change in chronic kidney disease course, which is associated with increased circulating MMP-2 levels [4,5,6]. These alterations clearly promote vascular medial layer calcification [6], and the increases in MMP-2 levels correlated positively with vascular stiffness and phosphate concentrations in chronic kidney disease patients [25]. In line with our results showing increased MMP-2 and TIMP-2 levels in ESKD patients, elevated circulating MMP-2 and TIMP-2 levels have been described as an indicator of CVD in dialysis patients [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, experimental evidence showed an early upregulation of MMP-2 expression in areas of elastin degradation and smooth muscle cells phenotype change in chronic kidney disease course, which is associated with increased circulating MMP-2 levels [4,5,6]. These alterations clearly promote vascular medial layer calcification [6], and the increases in MMP-2 levels correlated positively with vascular stiffness and phosphate concentrations in chronic kidney disease patients [25]. In line with our results showing increased MMP-2 and TIMP-2 levels in ESKD patients, elevated circulating MMP-2 and TIMP-2 levels have been described as an indicator of CVD in dialysis patients [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…This process includes enhanced arterial calcification and activation of fibroblasts and cytokines, eventually leading to vascular extracellular matrix remodeling [4,5]. While growing evidence suggests that MMP abnormalities are involved in the vascular changes associated with kidney failure [6], a particular imbalance between MMP-2 and its endogenous inhibitor, TIMP-2, has been implicated in the vascular alterations of ESKD[7]. Previous studies showed altered MMP-2 and TIMP-2 levels in dialysis patients, thus suggesting a mechanism for cardiovascular disease (CVD) complications in these patients [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] As well as leading to a loss of arterial compliance, per se, elastin degradation also appears to be a precursor to mineralization, 15 priming the vessel wall for calcification through the release of elastin peptide fragments (or elastinderived peptides [EDPs]) that induce osteogenic responses in VSMCs 16 and by providing a nidus for mineral crystal growth. Because there is now strong evidence that elastin degradation may play an important role in vascular disease, we hypothesized that higher circulating cathepsin S, MMP-2, and EDP levels would be associated with increased mortality in our cohort of 200 patients with predialysis CKD.…”
mentioning
confidence: 99%
“…30) Furthermore, lumican-transfected pancreatic cancer cells were reported to secret 70 kDa lumican (KS-GAG-rich lumican) and to decrease the production of MMP-9.…”
Section: Discussionmentioning
confidence: 99%